Examining elite parasport athletes with sport involvement and sports equipment - Hambrick, M. E.; Hums, M. A.; Bower, G. G.; Wolff, E. A. (Adapted Physical Activity Quarterly, 2015)
Elite athletes require the most advanced sports equipment to maintain their competitive edge, but manufacturers cannot always satisfy these athletes` specific equipment needs. Sport involvement can influence sports-equipment selections and is described as the process by which individuals rely on attitudes and belief systems to make sports-related consumption decisions. This study involved semistructured interviews with 5 elite Parasport athletes to identify and analyze the role of sport involvement in their selection of sports equipment. The results revealed that the athletes identified product limitations, created a collaborative environment, and promoted a culture of innovation to develop new sports products and address existing limitations. Theoretical and practical implications are discussed.